Influence of seed layers on optical properties of aluminum in the UV range - Stempfhuber, Sven; Felde, Nadja; Schwinde, Stefan; Trost, Marcus; Schenk, Paul; Schroeder, Sven; Tuennermann, Andreas (Optics Express, 2020)
The potential of titanium and copper seed layers to enhance the optical properties of aluminum films for ultra-violet (UV) applications is analyzed. The seed layers significantly influence the initial layer growth of aluminum films. For the titanium-seeded aluminum, a surface roughness of 0.34 nm was observed. UV spectral reflectance measurements showed an average higher reflectivity of 4.8% for wavelengths from 120 nm to 200 nm for the aluminum film grown on the titanium seed layer. Furthermore, the titanium-seeded aluminum coatings were stable at an elevated temperature of 225°C and showed no increase in surface roughness or pinholes.
CRIS-Team Scopus Importer:2023-04-20